Thoughts about Time-Rhythm and the transition between Spoken and Sung Word in Musical Theatre (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This work proposes thoughts about the concept of Time-Rhythm and some of its possibilities in Musical Theatre, especially with regard to the transition between Spoken and Sung Words. We present a contextualization of this concept, first raising definitions of Time and Rhythm separately, since their definitions used in Music and Theatre, going through Stanislavski and the development of the Time-Rhythm concept itself, up to the dialogue with other researchers on the subject, such as Jerzy Grotowski, Renato Ferracini and Jacyan Castilho. Finally, we present possibilities for the relationship between Time-Rhythmand the transition between Spoken and Sung Words in Musical Theatre shows.
Keywords: Time-Rhythm; Musical Theatre; transition; spoken Word; sung Word